Thalasseleotrididae, new family of marine gobioid fishes from New Zealand and temperate Australia, with a revised definition of its sister taxon, the Gobiidae (Teleostei: Acanthomorpha) - Gill, Anthony C.; Mooi, Randall D. (Zootaxa, 2012)
Thalasseleotrididae n. fam. is erected to include two marine genera, Thalasseleotris Hoese & Larson from temperate Aus-tralia and New Zealand, and Grahamichthys Whitley from New Zealand. Both had been previously classified in the familyEleotrididae. The Thalasseleotrididae is demonstrably monophyletic on the basis of a single synapomorphy: membraneconnecting the hyoid arch to ceratobranchial 1 broad, extending most of the length of ceratobranchial 1 (= first gill slitrestricted or closed). The family represents the sister group of a newly diagnosed Gobiidae on the basis of five synapo-morphies: interhyal with cup-shaped lateral structure for articulation with preopercle; laterally directed posterior processon the posterior ceratohyal supporting the interhyal; pharyngobranchial 4 absent; dorsal postcleithrum absent; urohyalwithout ventral shelf. The Gobiidae is defined by three synapomorphies: five branchiostegal rays; expanded and medially-placed ventral process on ceratobranchial 5; dorsal hemitrich of pelvic-fin rays with complex proximal head. This studyrepresents a contribution to our ongoing clarification of the family Eleotrididae, which has served historically as a repository for genera not classified among the more derived gobioids (= Gobiidae as defined here).